Does hedge accounting reduce earnings volatility? Evidence from the implementation of MFRS no. 9 in Malaysia two export-oriented industries - Soh, Siong Ching (2020)
The objective of this research is to explore how the use of derivatives can affect the earnings volatility of Malaysian companies. Besides, this research aims to analyse the tendency of Malaysian companies in employing hedge accounting. Most importantly, this research also aims to determine how the use of hedge accounting and MFRS No. 9 adoption can impact the earnings volatility of Malaysian companies. This research uses a sample of 52 non-financial listed companies on Bursa Malaysia over a period of two years from 1st January 2017 to 31st December 2018. These 52 companies are from two export-oriented industries, namely, the electrical and electronics industry and the wood & wood products and furniture industry.